Case Report: A case of Vulvar Paget’s disease and literature review - Wang, Guojie (Frontiers in Oncology, 2025)
IntroductionVulvar Paget’s disease (VPD) is a rare vulvar malignant tumor commonly observed in postmenopausal females. VPD cases are mainly treated by surgery, and the postoperative recurrence rate is high. Owing to the absence of any specific clinical manifestations, VPD is often misdiagnosed as eczematous skin lesions, which leads to diagnostic delay.Case presentationA 63-year-old woman experienced vulvar itching for over 4 months after 15 years of menopause. Computed tomography scans revealed a slightly friable vulva. Gynecological examination detected that the bilateral labia majora, especially the right labia majora, were exposed to light skin pigmentation; a red spot with a diameter of 5cm was observed outside the right labia majora, with visible scratch marks. The pathological results of the vulvar biopsy indicated Paget’s disease. The patient received local vulvectomy, vulvar skin flap transplantation, and vulvar plastic surgery. Routine gynecological examination and radiological examination indicated negative results 3 years after the surgery. Moreover, neither local recurrence nor distant metastasis was recorded.ConclusionVPD is commonly misdiagnosed as its clinical manifestations are nonspecific, mimicking other dermatological diseases. The diagnosis of VPD relies on pathological examination. Surgical treatment is preferred for its treatment, but the recurrence rate is high. Hence, early diagnosis and postoperative follow-up are critical in VPD treatment. Early diagnosis and treatment can improve the survival and quality of life of VPD patients.